Dual-phase high carbon steel winding wire and its manufacturing method

The double-phase high carbon steel winding material, with its optimized chemical composition and microstructure, addresses the issues of tensile performance and fatigue life in existing winding wire products, achieving enhanced tensile performance and fatigue life.

JP2025511468APending Publication Date: 2025-04-16ANGANG STEEL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024551562
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-06
Filing Date
2022-05-10
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing winding wire products made from high carbon steel lack optimal tensile performance and fatigue life, primarily due to inadequate control over dislocation density and perlite lamellar spacing.

Method used

A double-phase high carbon steel winding material with a specifically designed chemical composition and microstructure, featuring a perlite lamellar structure with controlled lamellar spacing and a perlite pellet structure, optimized through precise cooling steps and rolling processes.

Benefits of technology

The solution significantly enhances the tensile performance and fatigue life of winding wires by reducing stress concentration and maintaining optimal dislocation density, while ensuring the strength requirements of the steel wires are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511468000001
    Figure 2025511468000001
  • Figure 2025511468000002
    Figure 2025511468000002
  • Figure 2025511468000003
    Figure 2025511468000003
Patent Text Reader

Abstract

The present invention provides a dual-phase high carbon steel winding wire rod and a manufacturing method thereof. The winding wire rod contains, by mass%, 0.60% to 0.65% C, 0.15% to 0.25% Si, 0.47% to 0.58% Mn, 0.0030% to 0.015% P, 0.0020% to 0.015% S, 0.0015% to 0.0060% N, 0.01% to 0.04% Cr, 0.01% to 0.04% Ni, The high carbon steel wire rod provided by the present invention is manufactured by using a corresponding manufacturing process and has a dual phase structure of pearlite lamellar structure and pearlite pellet structure. The fatigue life of the automobile control wire with a diameter of 0.14 mm reaches 20,000 times, and the quality of the winding wire rod meets the user's requirements for the fatigue life of high-grade automobile control wire.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of winding wire products, and in particular to dual phase high carbon steel winding wire and methods for its manufacture. [Background technology]

[0002] High carbon steel wire rods used in the manufacture of steel cords, tire bead wires, automobile control wires, elevator ropes, etc., must have high strength and excellent service performance to meet the requirements for safe operation of automobiles and other mechanical equipment. The metal structure of these wound wire rods is fine pearlite, and the fine pearlite lamellar structure increases the tensile strength of the wound wire rods. During the pulling process of the wound wire rods, the fine pearlite lamellae are gradually refined, and the dislocation density in the ferrite gradually increases, thereby increasing the strength of the steel wire. If the dislocation density is too high, it is easy to grow into fine cracks, which will reduce the tensile performance and service performance of the wound wire rods. Therefore, in the chemical composition design and organizational design of the wound wire rods, the requirements for the strength and service performance of the wound wire rods must be taken into consideration together to meet the quality requirements of users.

[0003] The invention of Patent Document 1 (Chinese Patent Application No. 202110301478.8), which belongs to the technical field of steel wire rod and relates to a SWRH82B high carbon steel wire rod and its manufacturing method, provides a SWRH82B high carbon steel wire rod and its manufacturing method in order to solve the problems of an increase in the number of aluminum oxide inclusions, low purity of molten steel, and poor composition uniformity in the existing SWRH82B high carbon steel wire rod manufacturing process. The manufacturing method includes a primary refining process → LF refining process → continuous casting process → heating rolling process → controlled cooling process. The invention extrudes the final certified SWRH82B wire rod through production management of the primary refining furnace, control of the refining slag system, and reasonable continuous casting process parameters. The invention does not deoxidize aluminum in the entire process, so that the purity of the molten steel is high, and the obtained molten steel and billet meet the requirements of purity and composition uniformity. The present invention has the advantages of high efficiency and low cost. The low-fold segregation index of the obtained billet reaches within 1.05, the net carbon of the wire rod reaches within grade 2, and the martensite phase reaches within grade 1.5, which can meet the tensile requirements.

[0004] The application focuses on optimizing the manufacturing process of the windings to enhance the tensile performance of the windings, but does not consider the fatigue life of the windings made into metal products. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] China Patent Application Publication No. 113061688 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in consideration of the above technical problems, and provides a dual-phase high carbon steel winding wire rod and a manufacturing method thereof. The present invention proposes a dual-phase high carbon steel winding wire rod that is designed from the two aspects of chemical composition and microstructural state, and that satisfies the fatigue life quality of automotive control wires made from the winding wire rod. [Means for solving the problem]

[0007] The technical means adopted in the present invention are as follows. The dual-phase high carbon steel winding wire rod according to one embodiment of the present invention has, by mass%, C: 0.60% to 0.65%, Si: 0.15% to 0.25%, Mn: 0.47% to 0.58%, P: 0.0030% to 0.015%, S: 0.0020% to 0.015%, N: 0.0015% to 0.0060%, Cr: 0.01% to 0.04%, Ni: 0.01% to 0.04%, and % to 0.04%, Cu: 0.01% to 0.04%, As: 0.0008% to 0.005%, Sn: 0.0001% to 0.0005%, Ti: 0.0001% to 0.0005%, total oxygen: 0.0008% to 0.0020%, acid-soluble aluminum: 0.0001% to 0.0015%, and the balance being iron and unavoidable impurities. The dual phase structure is a pearlite lamellar structure and a pearlite pellet structure. The pearlite lamellar structure includes pearlite with small lamellar spacing and pearlite with large lamellar spacing, and the pellet structure includes coarse pearlite pellets and fine pearlite pellets.

[0008] Furthermore, the total of Ni, Cu and Cr accounts for 0.04% to 0.10% of the total mass.

[0009] The present invention manufactures a winding wire consisting of pearlite with small lamellar spacing and pearlite with large lamellar spacing by designing the chemical composition and cooling process. The pearlite with large lamellar spacing reduces the stress concentration of the winding wire during the pulling process, preventing tensile fracture caused by too high dislocation concentration in ferrite, and improving the tensile performance of the winding wire and the fatigue life of the manufactured metal products. The pearlite with small lamellar spacing ensures that the strength of the steel wire meets the requirements of users. The above pearlite with small lamellar spacing and pearlite with large lamellar spacing constitute a nano-scale multi-phase structure of the winding wire, making the winding wire have excellent comprehensive performance.

[0010] If the pearlite lamellar spacing of the wound wire is too small, the dislocation density in the ferrite structure during the pulling process will be too large, which will easily cause fine cracks and lead to tensile fracture of the wound wire. If the pearlite lamellar spacing is too large, the tensile strength of the steel wire cannot meet the user's requirements. In the actual manufacturing process of the wound wire, in order to ensure that the pearlite lamellar spacing meets the control range, it is necessary to keep the median value of the pearlite lamellar spacing of the wound wire within a certain range. The wound wire has stable tensile performance in this range. In order for the wound wire to form a multi-phase structure at the nanoscale, it is necessary to keep the standard deviation of the pearlite lamellar spacing of the wound wire within a certain range. If the standard deviation is too small, the difference in the pearlite lamellar spacing of the wound wire will be too small, which will not meet the comprehensive requirements of the tensile performance of the wire, the fatigue life of the product, and the tensile strength of the steel wire. If the standard deviation of the pearlite lamellar spacing of the wound wire is too large, it will lead to an excessively large wound wire structure, which will easily cause tensile fracture of the wound wire. Therefore, the winding wire has a pearlite lamellar spacing of 0.18 to 0.26 μm, a median of 0.20 to 0.25 μm, and a standard deviation of 0.015 to 0.035.

[0011] The present invention ensures that the wound wire structure is composed of coarse and fine pearlite pellets through chemical composition design, heating process, and rolling and cooling process. The coarse pearlite pellets improve the coordinated deformation ability of the wound wire during the pulling process, and increase the tensile performance of the wound wire and the fatigue life of the metal products produced. The fine pearlite pellets ensure that the steel wire produced by the wound wire meets the tensile strength requirements. The coarse and fine pearlite pellets constitute a multi-phase structure on a micro-scale of the wound wire, and ensure that the wound wire has excellent overall performance.

[0012] If the size of the pearlite pellets in the wound wire is too small, the work hardening will be significant during the pulling process, which will easily lead to the tensile fracture of the wound wire, and if the size of the pearlite pellets is too large, the tensile strength of the steel wire cannot meet the user's requirements. In the actual manufacturing process of the wound wire, in order to ensure that the size of the pearlite pellets meets the control range, it is necessary to keep the median size of the pearlite pellets in the wound wire within a certain range. The wound wire has stable processing performance within this range. In order for the wound wire to form a multi-phase structure on a microscale, it is necessary to keep the standard deviation of the size of the pearlite pellets in the wound wire within a certain range. If the standard deviation is too small, the difference in the size of the pearlite pellets will be too small, which will not meet the comprehensive requirements of the tensile performance of the wire, the fatigue life of the product, and the tensile strength of the steel wire. If the standard deviation of the size of the pearlite pellets in the wound wire is too large, it will lead to stress concentration in the wound wire during the pulling process, which will easily cause tensile fracture of the wound wire. Therefore, the winding wire is designed to restrict the size of the pearlite pellets to 19-53 μm, with a median of 28-41 μm and a standard deviation of 3.9-12.

[0013] By implementing the present invention, the high carbon steel wire rod has a dual phase structure of pearlite lamellar structure and pearlite pellet structure, so as to meet the quality requirements of users for the fatigue life of metal products.

[0014] The reasons for the selection and content design of each chemical component in the present invention are as follows:

[0015] C: Carbon in the wire is used to limit the strength of the winding wire and the product. If the carbon content is too low, the strength requirements of the steel wire cannot be met by the user, and if the carbon content is too high, the wire processing performance is reduced. Therefore, the carbon content in the present invention is limited to 0.60% to 0.65%.

[0016] Si: Silicon element is a strengthening element of ferrite, which increases the dislocation density of the steel wire during the drawing process, thereby increasing the strength of the steel wire. However, during the processing process, fine cracks are easily generated in the structure of the steel wire, which reduces the tensile performance of the winding wire and deteriorates the fatigue life of the product produced by the winding wire processing. Silicon element increases the eutectic transition temperature of the winding wire, improves the differentiation of the winding wire structure, and improves the tensile performance and service performance of the winding wire. In addition, silicon element, as the main deoxidizing element of high carbon steel, ensures that the total oxygen content of the winding wire meets the requirements of users. If the total oxygen content of the winding wire is too high, the fatigue life of the winding wire product cannot meet the requirements of users, so it is necessary to keep the silicon content in the steel constant. Therefore, in the present invention, the content of silicon element is limited to 0.15% to 0.25%.

[0017] Mn: Manganese element plays a role in lowering the eutectic transition temperature of steel and refining the wire structure, but if the manganese content is too high, it will lead to work hardening of the winding wire during the drawing process, which is disadvantageous to the cold working performance of the winding wire. Therefore, in the present invention, the manganese content is limited to 0.47% to 0.58%.

[0018] P: Phosphorus is a harmful element in steel and is prone to phosphorus segregation. Since serious phosphorus segregation reduces the fatigue life of products made from the winding wire, its content should not be too high. However, phosphorus element maintained at a certain amount in steel improves the differentiation of the winding wire structure and improves the tensile performance and service performance of the winding wire. Therefore, in the present invention, the content of phosphorus element is limited to 0.0030% to 0.015%.

[0019] S: Sulfides in steel have good deformability and can play a role in reducing the risk of other inclusions in steel. In addition, elemental sulfur improves the structural differentiation of the winding wire, and improves the tensile and service performance of the winding wire. However, if the content of elemental sulfur in steel is too high, it is likely to lead to interfacial separation between the inclusions and the winding wire substrate structure, which in turn deteriorates the tensile and service performance of the winding wire. Therefore, in the present invention, the content of elemental sulfur is limited to 0.0020% to 0.015%.

[0020] N: The nitrogen element in steel reduces the tensile performance of the winding wire, so it must be kept at a low level. However, the nitrogen element plays a role in inhibiting the decomposition of cementite, improving the service performance of the automobile control wire, and increasing the stability of the product during use. Therefore, in the present invention, the nitrogen element content is kept at 0.0015% to 0.0060%.

[0021] Cr: The chromium element in steel refines the pearlite lamellar spacing and plays a role in increasing the tensile strength of the winding wire. However, if the chromium element content in steel is too high, the winding wire undergoes significant work hardening during the tension process, which reduces the workability. Therefore, in the present invention, the chromium element content is limited to 0.01% to 0.04%.

[0022] Ni: Nickel element does not form carbides with carbon in steel. Nickel element exists in ferrite and austenite, refines ferrite granules, and lowers the ductile-brittle transition temperature of steel. However, nickel element in steel changes the phase transition temperature of winding wire and steel wire, causing strength fluctuation of steel wire, so it is necessary to control it. Therefore, in the present invention, the content of nickel element is limited to 0.01% to 0.04%.

[0023] Cu: Copper element enhances the strength of the winding wire material and the steel wire, so that the strength of the winding wire material and the steel wire meets the requirements of users. However, copper element changes the phase transition temperature of the winding wire material and the steel wire, which causes fluctuations in the processing performance of the steel wire after heat treatment, so it is necessary to control the content so that it is not too high. Therefore, in the present invention, the content of copper element is limited to 0.01% to 0.04%.

[0024] In order to realize the above-mentioned effects of nickel element, chromium element and copper element, the total content of Ni+Cu+Cr is preferably restricted to 0.04% to 0.10%.

[0025] As: Arsenic element is easy to be enriched in grain boundary in steel, reduce the energy of the system, and stabilize austenite. However, if the arsenic content in steel is too high, it may reduce the tensile performance of the winding wire and the fatigue life of the metal product. Therefore, the content of arsenic element in the present invention is limited to 0.0008% to 0.005%.

[0026] Sn: Tin element is easily segregated to grain boundaries in steel and stabilizes austenite. Furthermore, since the tin element segregated to grain boundaries reduces the performance of steel, it is necessary to suppress the tin content in steel within a certain range. Therefore, in the present invention, the content of tin element is suppressed to 0.0001% to 0.0005%.

[0027] Ti: Titanium element in steel tends to form titanium nitride inclusions with nitrogen element, which deteriorates the tensile performance and service performance of the winding wire. However, an appropriate amount of titanium element forms fine nitrides with nitrogen element, which plays a role in suppressing the expansion of microscopic cracks in the winding wire during tension and use. Therefore, the content of titanium element in the present invention is limited to 0.0001% to 0.0005%.

[0028] The acid-soluble aluminum in the steel reduces the melting point of the inclusions, makes the inclusions deformable, and reduces the adverse effect of the inclusions on the tensile and twisting properties of the winding wire. If the content of acid-soluble aluminum is too high, it will cause large alumina inclusions to form in the steel, which will reduce the tensile and service properties of the winding wire. Therefore, the content of acid-soluble aluminum in the present invention is limited to 0.0001% to 0.0015%.

[0029] If the oxygen content of the winding wire is too high, it will reduce the tensile and twisting performance of the winding wire. However, if the oxygen content is too low, it will be disadvantageous to control the inclusion composition and the breakage rate of the steel wire will increase during the process of pulling and twisting the wire. Therefore, in the present invention, the oxygen content is limited to 0.0008% to 0.0020%.

[0030] The present invention further provides a method for manufacturing a dual-phase high carbon steel winding wire, which includes the steps of converter smelting, outer furnace refining, continuous casting and rolling, billet heating, wire rolling and wire cooling. The main specific steps are as follows:

[0031] 1) Smelting: Molten iron + scrap steel are smelted in converter, the scrap steel is added at 2%~8%, Ni content in scrap steel reaches 0.01%~0.06%, Cr content reaches 0.01%~0.08%, Cu content reaches 0.01%~0.06%, and the scrap steel contains the above trace elements, so that the residual element content in the molten steel meets the requirements. The molten steel is smelted in converter, and then refined in LF furnace, the processing temperature of the molten steel in LF furnace is 1510~1580℃, and the refining time is 30~40 minutes. In the refining process, argon stirring is performed, and the refining and stirring argon flow rate is controlled to 300~500NL / min to homogenize the chemical composition of the molten steel and float the large granules of inclusions, and the molten steel is discharged. In the refining process, the oxygen activity is kept at 10-30 ppm, the sulfur content is kept at 0.0020%-0.013%, and nitrogen and other elements in the molten steel are reduced by using oxygen and sulfur, which are surface active elements.

[0032] 2) Continuous casting of blooms: After smelting the molten steel, continuous casting is performed. The cross-sectional size of the continuous casting billet is limited to (200~300)mm x (300~400)mm, and the cooling intensity of the secondary cooling of the continuous casting of blooms is limited to 0.2~0.4m. 3 / (h*t), the degree of superheat in the continuous casting tundish is kept below 25°C, the current strength in the electromagnetic stirring in the crystallizer during the continuous casting process is kept to 300A-450A, and the frequency in the electromagnetic stirring is kept to 1Hz-3Hz. The equiaxed crystal region of the continuous casting billet is made to occupy 25%-35% of the entire cross section (equiaxed crystal region + columnar crystal area), and the segregation index of carbon element at the junction of the columnar crystal and equiaxed crystal in the continuous casting billet is kept to 0.90-1.05. The above billet segregation control reduces the tensile fracture of the winding wire due to the interface segregation between the columnar crystal grains and equiaxed crystal grains.

[0033] 3) Continuous rolling of blooms: The total heating time is restricted to 3.5~4.3h, the temperature of the soaking zone is restricted to 1180~1240℃, and the soaking time is restricted to 40~60min, which lays the foundation for controlling the structure of the winding wire. The cross-sectional size of the continuous rolling square billet is restricted to (150~170)mm*(150~170)mm.

[0034] 4) Heating of continuous rolling billet: Heat the billet after continuous rolling, keeping the heating rate at 13℃ / min~18℃ / min, keeping the temperature of the soaking part at 1055~1150℃, keeping the soaking time at 35~50min, reducing the segregation of elements such as carbon, manganese, and sulfur through high temperature diffusion, and improving the structural uniformity of the rolled raw material for the winding wire. Keep the residual oxygen in the heating furnace at 2%~8%, adjust the atmosphere in the heating furnace to a slightly positive pressure, and keep the pressure at 2~9Pa. Maintain the oxidation in the heating furnace to prevent the deterioration of the peeling performance of the iron oxide film on the billet surface due to the reducing atmosphere, which will deteriorate the surface quality of the subsequent steel wire processing process and the service performance of the manufactured metal products.

[0035] 5) Rolling of the winding wire: After the billet is heated, it is removed from the heating furnace and dephosphorized with high-pressure water. The dephosphorization pressure is controlled to 14MPa or more to prevent deterioration of the surface quality of the winding wire. The billet goes through rough rolling, intermediate rolling, pre-finish rolling and finish rolling, and then undergoes wire-making to produce the winding wire. The finish rolling speed of the winding wire is controlled to 95-115m / s, the area reduction rate per pass during the finish rolling process is controlled to 15%-25%, and the deformation rate is controlled to 700s. -1 ~800s-1 The size and distribution index of pearlite pellets in the winding wire not only meet the fatigue life requirements of automotive control wires, but also lay the foundation for controlling the pearlite lamellar spacing of the winding wire. The wiremaking temperature of the winding wire is limited to 890-930℃, which lays the foundation for controlling the final structure of the winding wire. The diameter of the winding wire is 5.0-6.0mm.

[0036] 6) Cooling of winding wire: After winding, the cooling rate of winding wire is controlled to 7-15℃ / s, and the phase change time is controlled to 15-25s. The phase change temperature of winding wire is controlled to 650-690℃, so as to lay the foundation for controlling the pearlite lamellar spacing and pearlite pellet size of winding wire. Effect of the Invention

[0037] The present invention provides a dual-phase high carbon steel winding wire. The present invention manufactures a winding wire consisting of pearlite with small lamellar spacing and pearlite with large lamellar spacing by designing the chemical composition and cooling process. The pearlite with large lamellar spacing reduces the stress concentration of the winding wire during the pulling process, prevents tensile fracture caused by too high dislocation concentration in ferrite, and improves the tensile performance of the winding wire and the fatigue life of the metal product. The pearlite with small lamellar spacing ensures that the strength of the steel wire meets the requirements of the user. The above pearlite with small lamellar spacing and pearlite with large lamellar spacing constitute a nano-scale multi-phase structure of the winding wire, so that the winding wire has excellent comprehensive performance. The present invention ensures that the winding wire structure is composed of coarse pearlite pellets and fine pearlite pellets through chemical composition design, heating process, and rolling and cooling process. The coarse pearlite pellets improve the cooperative deformation ability of the winding wire during the pulling process, and improve the tensile performance of the winding wire and the fatigue life of the metal product produced. The fine pearlite pellets ensure that the steel wire made by the winding wire meets the tensile strength requirements. The coarse pearlite pellets and the fine pearlite pellets constitute the micro-scale multi-phase structure of the winding wire, so that the winding wire has excellent comprehensive performance. The automobile control wire manufactured by the winding wire of the present invention has a single wire with a thinnest diameter of 0.14 mm. The fatigue life of the automobile control wire is measured by a repeated load fatigue test using a 350N counterweight. The measurement results show that the fatigue life of the automobile control wire reaches at least 20,000 times, and the quality of the winding wire meets the user's requirements for the fatigue life of high-grade automobile control wire. In addition, the present invention supplements trace elements with scrap steel in the smelting process, saving the cost of additional smelting trace element metals, reducing the carbon emission of additional smelting, and achieving the reuse of scrap steel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be described more clearly and completely below, but it should be understood that the described embodiments are only some of the embodiments of the present invention, not all of the embodiments. Any other embodiments that a person skilled in the art can obtain based on the embodiments of the present invention without creative effort shall be included in the scope of protection of the present invention.

[0039] The chemical compositions and technical processes of the embodiments of the present invention are detailed in Table 1.

[0040] [Table 1-1]

[0041] [Table 1-2]

[0042] The winding wire produced in this embodiment is subjected to the process of dephosphorization-tension-heat treatment-tension-heat treatment-finish tension-twisting to produce an automobile control wire. The automobile control wire produced by the winding wire of the present invention has a minimum diameter of 0.14 mm. The fatigue life of the automobile control wire is measured by a repeated load fatigue test using a 350 N counterweight. The test results show that the fatigue life of the automobile control wire can reach at least 20,000 times, and the quality of the winding wire meets the user's requirements for the fatigue life of high-grade automobile control wire.

[0043] In the present invention, the meanings of the maximum value, minimum value, median value and standard deviation of the lamellar spacing of pearlite and the pellet size are as follows.

[0044] Maximum lamellar spacing of pearlite: After etching the cross section of the sample with a 4% nitric acid alcohol solution, the maximum thickness of the pearlite lamella perpendicular to the observation surface is measured by the vertical section method.

[0045] Maximum size of pearlite pellets: The cross section of the sample is etched with a 4% nitric acid alcohol solution, and then the maximum equivalent diameter of the pearlite pellets is measured.

[0046] Minimum lamellar spacing of pearlite: The cross section of the sample is etched with a 4% nitric acid alcohol solution, and then the minimum thickness of the pearlite lamella perpendicular to the observation surface is measured by the vertical cross section method.

[0047] Minimum size of pearlite pellets: The cross section of the sample is etched with a 4% nitric acid alcohol solution, and then the minimum equivalent diameter of the pearlite pellets is measured.

[0048] Median: The lamellar spacing of pearlite, which is the middle value in the array of measurement results for the pellet size.

[0049] Standard deviation: This represents the distribution of the lamellar spacing and pellet size of pearlite, and explains the degree of difference in the internal microstructural dimensions of pearlite.

[0050] Finally, the following should be mentioned: the above embodiments are only for explaining the technical means of the present invention, and are not limited thereto. Although the present invention has been described in detail with reference to the above embodiments, it is also possible to modify the technical means described in the above embodiments, or to carry out equivalent replacements for part or all of the technical features, and it is understood by those skilled in the art that the essence of the corresponding technical means does not depart from the scope of the technical means of the embodiments of the present invention through such modification or replacement.

[0051] (Additional Note) (Appendix 1) In mass%, C: 0.60%~0.65%, Si: 0.15%~0.25%, Mn: 0.47%~0.58%, P: 0.0030%~0.015%, S :0.0020%~0.015%, N:0.0015%~0.0060%, Cr:0.01%~0.04%, Ni:0.01%~0.04%, Cu:0 0.01%-0.04%, As: 0.0008%-0.005%, Sn: 0.0001%-0.0005%, Ti: 0.0001%-0.0005%, total oxygen: 0.0008%-0.0020%, acid-soluble aluminum: 0.0001%-0.0015%, and the remainder being iron and unavoidable impurities. 2. A winding wire material of dual phase high carbon steel.

[0052] (Appendix 2) The material has a dual phase structure including a pearlite lamellar structure and a pearlite pellet structure. 2. A dual-phase high carbon steel winding wire material according to claim 1.

[0053] (Appendix 3) The pearlite lamellar spacing is 0.18-0.26 μm, with a median of 0.20-0.25 μm and a standard deviation of 0.015-0.035. The size of the pearlite pellets ranged from 19 to 53 μm, with a median of 28 to 41 μm and a standard deviation of 3.9 to 12. 3. A dual-phase high carbon steel winding wire material according to claim 2.

[0054] (Appendix 4) The total content of Ni, Cu and Cr is 0.04% to 0.10% of the total mass. 2. A dual-phase high carbon steel winding wire material according to claim 1.

[0055] (Appendix 5) 1) A smelting process including converter smelting and extrafurnace refining, in which the oxygen activity is controlled to 10-30 ppm and the sulfur content is controlled to 0.0020%-0.013% during the refining process; 2) a continuous casting process in which the superheat of the continuous casting tundish is controlled to ≦25°C, the current strength of the electromagnetic stirring in the crystallizer during the continuous casting process is controlled to 300A-450A, the frequency of the electromagnetic stirring is controlled to 1Hz-3Hz, the equiaxed crystal ratio of the continuous casting billet is controlled to 25%-35%, and the segregation index of carbon element at the joint between the columnar crystal and the equiaxed crystal of the continuous casting billet is controlled to 0.90-1.05; 3) A continuous rolling process in which the total heating time is kept to 3.5 to 4.3 h, the temperature of the soaking zone is kept to 1180 to 1240 ° C, and the soaking time is kept to 40 to 60 min; 4) A billet heating process in which the billet after continuous rolling is heated, the heating rate is controlled to 13-18°C / min, the temperature of the soaking part is controlled to 1055-1150°C, and the soaking time is controlled to 35-50min; 5) After the billet is heated, it is taken out of the heating furnace and dephosphorized with high pressure water, the dephosphorization pressure is controlled to 14MPa or more, the billet goes through rough rolling, intermediate rolling, pre-finish rolling and finish rolling, and then a wire-making operation is carried out to produce a winding wire, and the winding wire-making temperature is controlled to 890-930°C. 6) after wire making, a winding material cooling process is included, in which the cooling rate of the winding material is controlled to 7 to 15°C / s and the phase change time is controlled to 15 to 25s; 5. A method for producing a dual-phase high carbon steel winding wire rod according to any one of claims 1 to 4.

[0056] (Appendix 6) In the smelting process, the molten iron and scrap steel are smelted in a converter, and the scrap steel contains Ni, Cr, and Cu. The molten steel is smelted in the converter and then refined in an LF furnace. The treatment temperature of the molten steel in the LF furnace is 1510-1580°C, the refining time is 30-40min, and argon stirring is performed during the refining process, and the flow rate of argon for refining and stirring is 300-500NL / min. The manufacturing method according to claim 5,

[0057] (Appendix 7) In the smelting process, the amount of added scrap steel is 2% to 8%. The manufacturing method according to claim 6,

[0058] (Appendix 8) We use a continuous bloom casting process and a continuous bloom rolling process. In the bloom continuous casting process, the cross-sectional size of the continuous casting billet is (200~300)mm*(300~400)mm, and the cooling intensity of the secondary cooling of the bloom continuous casting is 0.2~0.4m. 3 / (h*t), In the continuous rolling process of the bloom, the cross-sectional size of the continuous rolling rectangular billet is (150~170)mm*(150~170)mm; The manufacturing method according to claim 5,

[0059] (Appendix 9) In the billet heating process, the residual oxygen in the heating furnace is 2% to 8%, and the atmosphere in the heating furnace is slightly positive, and the pressure is 2 to 9 Pa. The manufacturing method according to claim 5,

[0060] (Appendix 10) In the rolling process of the winding wire, the finishing rolling speed of the winding wire is 95 to 115 m / s, the reduction in area per pass during the finishing rolling process is 15% to 25%, and the deformation rate is 700 s -1 ~800s -1 and The diameter of the winding wire obtained through the rolling process is 5.0 to 6.0 mm. The manufacturing method according to claim 5,

Claims

1. In mass%, C: 0.60% to 0.65%, Si: 0.15% to 0.25%, Mn: 0.47% to 0.58%, P: 0.0030% to 0.015%, S : 0.0020% to 0.015%, N: 0.0015% to 0.0060%, Cr: 0.01% to 0.04%, Ni: 0.01% to 0.04%, Cu: 0 0.01% to 0.04%, As: 0.0008% to 0.005%, Sn: 0.0001% to 0.0005%, Ti: 0.0001% to 0.0005%, total oxygen: 0.0008% to 0.0020%, acid-soluble aluminum: 0.0001% to 0.0015%, and the balance being iron and inevitable impurities.

2. A winding wire material of dual phase high carbon steel.

2. The material has a dual phase structure including a pearlite lamellar structure and a pearlite pellet structure.

2. The dual phase high carbon steel winding wire of claim 1.

3. The pearlite lamellar spacing is 0.18 to 0.26 μm, with a median of 0.20 to 0.25 μm and a standard deviation of 0.015 to 0.

035. The size of the pearlite pellets is 19-53 μm, with a median of 28-41 μm and a standard deviation of 3.9-12.

3. The dual phase high carbon steel winding wire of claim 2.

4. The total content of Ni, Cu and Cr is 0.04% to 0.10% of the total mass; 2. The dual phase high carbon steel winding wire of claim 1.

5. 1) A smelting process including converter smelting and extrafurnace refining, in which the oxygen activity is controlled to 10-30 ppm and the sulfur content is controlled to 0.0020%-0.013% during the refining process; 2) a continuous casting process in which the superheat of the continuous casting tundish is controlled to ≦25° C., the current strength of the electromagnetic stirring in the crystallizer during the continuous casting process is controlled to 300 A-450 A, the frequency of the electromagnetic stirring is controlled to 1 Hz-3 Hz, the equiaxed crystal ratio of the continuous casting billet is controlled to 25%-35%, and the segregation index of carbon element at the joint between the columnar crystal and the equiaxed crystal of the continuous casting billet is controlled to 0.90-1.05; 3) A continuous rolling process in which the total heating time is limited to 3.5 to 4.3 hours, the temperature of the soaking part is limited to 1180 to 1240°C, and the soaking time is limited to 40 to 60 minutes; 4) a billet heating process in which the billet after continuous rolling is heated, the heating rate is controlled to 13 to 18 ° C / min, the temperature of the soaking part is controlled to 1055 to 1150 ° C, and the soaking time is controlled to 35 to 50 minutes; 5) After the billet is heated, it is taken out of the heating furnace and dephosphorized with high pressure water, the dephosphorization pressure is controlled to 14 MPa or more, the billet undergoes rough rolling, intermediate rolling, pre-finish rolling and finish rolling, and then a wire-making operation is carried out to produce a winding wire material, and the winding wire material wire-making temperature is controlled to 890-930°C. 6) a winding wire cooling process in which the cooling rate of the winding wire is controlled to 7 to 15° C. / s and the phase change time is controlled to 15 to 25 s after the wire making process; A method for manufacturing a dual-phase high carbon steel winding wire rod according to any one of claims 1 to 4.

6. In the smelting process, the molten iron + scrap steel is smelted in a converter, the scrap steel contains Ni, Cr and Cu, the molten steel is smelted in the converter and then refined in an LF furnace, the treatment temperature of the molten steel in the LF furnace is 1510-1580°C, the refining time is 30-40 min, argon stirring is performed during the refining process, and the argon flow rate for refining and stirring is 300-500 NL / min. The method according to claim 5 .

7. In the smelting process, the amount of added scrap steel is 2% to 8%; The method according to claim 6 .

8. We use a continuous bloom casting process and a continuous bloom rolling process. In the bloom continuous casting process, the cross-sectional size of the continuous casting billet is (200-300) mm*(300-400) mm, and the cooling intensity of the secondary cooling of the bloom continuous casting is 0.2-0.4 m 3 / (h*t), In the continuous rolling process of the bloom, the cross-sectional size of the continuous rolling rectangular billet is (150-170) mm * (150-170) mm; The method according to claim 5 .

9. In the heating process of the billet, the residual oxygen in the heating furnace may be 2% to 8%, and the atmosphere in the heating furnace is slightly positive, and the pressure is 2 to 9 Pa. The method according to claim 5 .

10. In the rolling process of the winding wire, the finishing rolling speed of the winding wire is 95 to 115 m / s, the reduction in area per pass during the finishing rolling process is 15% to 25%, and the deformation rate is 700 s -1 ~800s -1 and The diameter of the winding wire obtained through the rolling process of the winding wire is 5.0 to 6.0 mm. The method according to claim 5 .

Citation Information

Patent Citations

  • High strength wire rod excellent in delayed fracture resistance and forgeability and / Or under head toughness and its producing method

    JP2001294981A

  • Wire rod having excellent wire drawability and its production method

    JP2007327084A

  • Hot-rolled wire rod having excellent wire drawability and mechanical descaling property, and method for producing the same

    JP2010132943A

  • High carbon steel wire rod and method for manufacturing same

    US20160145712A1

  • High-carbon steel wire rod and method for manufacturing same

    WO2014208492A1